Development of a Socio-Scientific-Based Language Learning Model to Improve Argumentative Writing Skills in Senior High School - Pohan, Jusrin Efendi; Trianton, Teguh; Telaumbanua, Sadieli; -, Rudy (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This study is motivated by the low ability of students in writing argumentation in its elements. This can be seen from the assignment given that there is still a lack of connection between the substance and reality, making the content of the argumentation conveyed ambiguous to the reader. The goal is to develop a theoretical model of socio-scientific-based language learning. The issues or problems used are adjusted to the concept or theory of language in use, such as the issue of hate speech in forensic linguistics, the issue of cultural immersion in anthropolinguistics, and so on. This type of research is development research, which develops research products and is tested on a test class. This research was conducted at SMA Negeri 2 Medan City, which contained a research sample of 35 students. The products tested were SCC-based language learning model books, teachers' books, and students' books. The research instruments used consisted of a/questionnaire, an interview guide, and an observation guide. Data analysis was done qualitatively and quantitatively according to the type of data obtained. The results of this study indicate that the research products tested in both limited and large classes achieved an expert validation percentage of 89.42% and a practicality value of 81.95%. Furthermore, the effectiveness of the model is evident from the increase in student learning activities.